Blue magic : the people, power, and politics behind the IBM personal computer - Chposky, James. 4 0 16; Leonsis, Ted.; 5 (New York : Facts on File, 1988)
The story of how America's largest corporation broke with its traditions to produce the IBM PC.
Includes index.
Booklist
Adult;Adult
Keywords: 2 -- 0; History. -- International Business Machines Corporation -- 6; History.;History.;History.;History. -- IBM microcomputers;IBM Personal Computer;IBM microcomputers;IBM Personal Computer; 20; 2